Diskursus Publik Terhadap Transportasi Berkelanjutan: Studi Kasus Elektrifikasi Moda Transportasi di DKI Jakarta - Nugroho, Aris; Prasetyo, Satria; Damarjati, Cahya; Rochmah, Faizatur (Nakhoda: Jurnal Ilmu Pemerintahan, 2024)
The policy of electrification of transportation modes in DKI Jakarta has created debate among the public, especially on social media. The policy of creating an environmentally friendly electric transportation ecosystem is not accompanied by supporting aspects of sustainable transportation. This research explores this debate by linking it to aspects of sustainable transportation, such as the environment, society, and economy, to understand and assess the development of transportation electrification. The qualitative method used in this research is a Q-Das approach using NVivo 12 Plus as software that helps collect and analyze data found on social media. The study found that the public needs to view transportation electrification policies as fully sustainable. Firstly, in the social dimension, the public criticized the policy of transitioning transportation to electricity without being accompanied by an energy transition as a "false solution". This is based on the energy source for electric transportation originating from coal-fired power plants, which are also the main contributors to pollutants. Second, in the economic dimension, the public views that the massive electric transportation ecosystem still needs to be supported by supporting aspects such as the availability of SPKLU. The estimated time for recharging batteries, which is relatively long compared to refueling conventional transportation, is considered to hamper and influence public economic activities. In the environmental dimension, the public criticizes that if a massive transportation electrification policy is carried out, it will require excessive electricity use. This is seen as inefficient and creates new problems that previously stemmed from excessive fuel use.